CEO Characteristics and ESG Disclosure: An Indonesian Evidence - Akbar, Henisa Fatmawati; Purnomowati, Nasyiah Hasanah (Advances in Social Sciences Research Journal, 2026)
This paper purposes to investigate the influence of the characteristics of the Chief Executive Officer (CEO) on Environmental, Social, and Governance (ESG) disclosure for public companies in Indonesia. This research is constructed from the Upper Echelon Theory, which investigates the effect of age, tenure, and educatio of the CEO on ESG disclosure. The research uses a panel data set of 219 firm-year observations of public companies from Indonesia from 2020 to2022, and ESG scores from the Refinitiv database. This study employs a panel data regression with robust standard errors as the empirical method. The results of the study reveal that the age of the CEO is not a factor for ESG disclosure, but the tenure of the CEO is negative for ESG disclosure. On the other hand, the educational background of the CEO, if in the field of engineering, is positive for ESG disclosure. Therefore, it can be concluded that the current study is an extension of the existing ESG literature, providing empirical evidence and adding the factor of educational background of the CEO as an important factor for ESG disclosure.